Designing A 7P Marketing Mix Strategy To Boost Sales: A Case Study At Maqdisa Beauty Salon - Hapsari, Yunita Dwi; Radianto, Wirawan Endro Dwi (BIMA Journal (Business, Management, & Accounting Journal), 2025)
Purpose: This study aims to design an integrated marketing strategy based on the 7P marketing mix to improve sales performance and customer engagement in beauty salons, particularly in regional areas of Indonesia that face increasing market competition. Methodology: A qualitative case study was conducted at Maqdisa Beauty Salon in Ngawi, East Java. Data were collected through semi-structured interviews, direct observations, and documentation involving seven informants, including salon staff and loyal customers. Thematic analysis was conducted using NVivo 15. Results: The study produced a strategic 7P marketing model, including product innovation and service diversification, affordable pricing and bundling, strategic location, digital promotions, staff development, improved service processes, and enhanced physical atmosphere. The integrated implementation of these elements helped address sales instability and improve customer satisfaction. Novelty: Unlike prior studies that examined 7P elements in isolation, this study presents a holistic application of the full marketing mix in a local business context. Originality: It offers a practical, replicable model specifically for small-scale beauty salons in emerging markets. Conclusion: An integrated 7P strategy can effectively enhance customer loyalty, service quality, and business sustainability. The findings offer practical guidance for similar service enterprises operating in competitive regional environments. Type of Paper : Case Study/ Qualitative Research.